An analysis of land management stakeholders in Lushoto (Tanzania) and Ntcheu (Malawi). - Rosendahl, Judith (International Center for Tropical Agriculture, 2018)
Widespread land degradation has serious negative ecological, social, and economic consequences. This is particularly true for smallholder farming systems in sub-Saharan Africa, which are crucial for the livelihoods of the majority of the population and the national economies. Sustainable land management (SLM) is seen as the best way to combat or even reverse land degradation. However, the contexts and conditions hindering land users’ uptake of SLM techniques are often poorly understood. The AGORA project explores the drivers of land degradation at two sites in Tanzania and Malawi. It focuses on the social and economic hindrances to the adoption of SLM practices. This Working Paper presents key findings of a stakeholder analysis of both sites. The analysis builds on interviews, a stakeholder workshop, and NetMap outputs. It sheds light on particular challenges, especially a lack of support, for successful sustainable land management by smallholders in both sites. Potentials and entry points for improvement lie in existing knowledge on SLM and attempts for coordination of service providers. Some findings were used to initiate a stakeholder engagement process that aims to enhance SLM in the two regions.